2007
DOI: 10.1080/14789940601108439
|View full text |Cite
|
Sign up to set email alerts
|

Understanding change in a therapeutic community: An action systems approach

Abstract: This study aims to provide a framework for assessing and modelling behavioural changes in a prison therapeutic community. A behavioural checklist able to monitor both positive and negative behaviours throughout the course of therapy, paying particular attention to offence-paralleling behaviours, was devised. Content analysis of therapy notes on n=68 residents identified 35 variables. The study investigated the hypothesis that it is possible to model behavioural change over the course of therapy using an action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Research has demonstrated post-treatment improvements in self-reported positive change (Miller, Sees & Brown., 2006); personality change (e.g., decreased levels of hostility, neuroticism, and psychoticism) (Newton, 1998); increased employment and reductions in drug use (Messina, Wish & Nemes, 2000); decreased custodial disciplinary charges within and post TC (Cooke, 1989;Hodkin & Woodward, 1996); and reduced adherence to conventional prisoner attitudes (Genders & Player, 1995). Neville, Miller, and Fritzon (2007) conducted an interesting study involving the development and use of a check-list to evaluate behavioral change in 30 TC based offenders. A number of outcomes were reported including an increase in offenders' engagement in 'functional' behaviors, such as asking others for advice and being supportive of one another, and a decrease in dysfunctional behaviors, such as becoming angry or disruptive and being "anti-staff".…”
mentioning
confidence: 99%
“…Research has demonstrated post-treatment improvements in self-reported positive change (Miller, Sees & Brown., 2006); personality change (e.g., decreased levels of hostility, neuroticism, and psychoticism) (Newton, 1998); increased employment and reductions in drug use (Messina, Wish & Nemes, 2000); decreased custodial disciplinary charges within and post TC (Cooke, 1989;Hodkin & Woodward, 1996); and reduced adherence to conventional prisoner attitudes (Genders & Player, 1995). Neville, Miller, and Fritzon (2007) conducted an interesting study involving the development and use of a check-list to evaluate behavioral change in 30 TC based offenders. A number of outcomes were reported including an increase in offenders' engagement in 'functional' behaviors, such as asking others for advice and being supportive of one another, and a decrease in dysfunctional behaviors, such as becoming angry or disruptive and being "anti-staff".…”
mentioning
confidence: 99%
“…4 For similar applications of the action system theory to psychotherapy, see Neville et al (2007) study on prison therapeutic community. 5 Cf.…”
Section: The Expressive Functioning Mode In Therapymentioning
confidence: 99%
“…This model is largely the one proposed by McDougall and colleagues (1994). Similarly, Neville et al (2007) have developed a behavioural checklist containing 35 'single-event' variables that purportedly assists monitoring of both 'positive' and 'negative' behaviours throughout the course of therapy, paying particular attention to OPBs using content analysis of therapy notes.…”
Section: Single Eventsmentioning
confidence: 99%
“…Behaviour at the time of the offence is identified as being topographically similar to current behaviour simply because it has the same form or appearance as behaviour at the time of the offence. Checklist-based approaches such as McDougall and Clark's (McDougall & Clark, 1991) and Neville's (Neville et al, 2007) are topologically oriented and do not attempt to identify linkages based on function of behaviour or some other underlying psychological cause.…”
Section: Topological Similaritymentioning
confidence: 99%